Radial drift of dust in protoplanetary discs: the evolution of ice lines and dead zones - Cridland, Alex J.; Pudritz, Ralph E.; Birnstiel, Tilman (Monthly notices of the Royal Astronomical Society, 2017)
We have developed a new model for the astrochemical structure of a viscously evolving protoplanetary disc that couples an analytic description of the disc's temperature and density profile, chemical evolution and an evolving dust distribution. We compute evolving radial distributions for a range of dust grain sizes, which depend on coagulation, fragmentation and radial drift processes. In particular, we find that the water ice line plays an important role in shaping the radial distribution of the maximum grain size because ice-coated grains are significantly less susceptible to fragmentation than their dry counterparts. This in turn has important effects on disc ionization and therefore on the location of dead zones. In comparison to a simple constant gas-to-dust ratio model for the dust as an example, we find that the new model predicts an outer dead zone edge that moves in by a factor of about 3 at 1 Myr (to 5 au) and by a factor of about 14 by 3 Myr (to 0.5 au). We show that the changing position of the dead zone and heat transition traps have important implications for the formation and trapping of planets in protoplanetary discs. Finally, we consider our results in light of recent Atacama Large Millimeter Array observations of HL Tau and TW Hya.